Analisis Financial Distress pada Perusahaan Sektor Food & Beverage yang Terdaftar di Bursa Efek Indonesia dengan Menggunakan Model Ohlson, Taffler, Fulmer, Zavgren dan Zmijewski Periode 2020-2024 - Intan Kelana; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the accuracy of financial distress prediction models, namely the Ohlson, Taffler, Fulmer, Zavgren, and Zmijewski models, in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The sample consisted of 30 companies. Data analysis used five models, and accuracy testing was performed using Microsoft Excel. The results showed differences, with the Zavgren model having the highest accuracy of 97%, while the Zmijewski model had the lowest accuracy of 67%. PT Bumi Teknokultura Unggul Tbk, PT Estika Tata Tiara Tbk, PT Dua Putra Utama Makmur Tbk, PT Sentra Food Indonesia Tbk, and PT Jaya Agra Wattie Tbk are companies that are consistently predicted to experience financial distress due to commodity price volatility, climate change, industry slowdown, high operational costs, dependence on imports, weak cash flow, and heavy debt burdens. Management responded with debt restructuring, changes in control and governance, asset sales, and strengthening liquidity and capital.